2006
DOI: 10.1094/cc-83-0093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Location in the United States on Amylose Content, Amylopectin Fine Structure, and Thermal Properties of Starches of Long Grain Rice Cultivars

Abstract: Starch was isolated from kernels of 27 rice samples consisting of nine U.S. long grain rice cultivars grown in three different locations (Missouri, Arkansas, Texas). Amylose (AM) content of the starches and the fine structure of the respective amylopectin (AP) were determined and used to explain differences observed in gelatinization properties. The AM content of rice cultivars grown at the lower temperature Missouri location increased 0.4–3% and 0.5–4% when compared with the same rices grown in Arkansas and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 25 publications
7
47
0
1
Order By: Relevance
“…In this study, the highest GCR value was displayed in late transplanting and lowest in ordinary, and 'Joami' showed higher value than 'Unkwang' in all transplanting times. These results coincide well with previous studies, showing that high temperature at the grain filling stage influences the physicochemical property such as protein and amylose content (Aboubacar et al, 2006). Jin et al (2005) evaluated the influence of the temperatures at the filling stage on the activities of key enzymes related to grain starch synthesis to understand how temperature influences the biochemical characteristics, and showed that starch synthesis is dependent on temperature.…”
Section: Meteorological Datasupporting
confidence: 90%
“…In this study, the highest GCR value was displayed in late transplanting and lowest in ordinary, and 'Joami' showed higher value than 'Unkwang' in all transplanting times. These results coincide well with previous studies, showing that high temperature at the grain filling stage influences the physicochemical property such as protein and amylose content (Aboubacar et al, 2006). Jin et al (2005) evaluated the influence of the temperatures at the filling stage on the activities of key enzymes related to grain starch synthesis to understand how temperature influences the biochemical characteristics, and showed that starch synthesis is dependent on temperature.…”
Section: Meteorological Datasupporting
confidence: 90%
“…As tools for starch research have become more sophisticated, and the relevance of rice as a cereal crop continues to increase, the literature has also become more plentiful with articles reporting the impact of G × E effects on rice starch composition and properties; a summary of which is given in Table . These works examined the various aspects of starch in milled rice: fine structure ; amylose and other chemical contents ; pasting, gelatinization, and retrogradation behavior ; milling yields and milled rice appearance ; and cooking and sensory characteristics . Amylose content was the most frequently used, starch‐related quantitative trait as it is also the most widely used indicator of rice grain quality.…”
Section: Genotype–environment Effects On Starch Structurementioning
confidence: 99%
“…With some exceptions, these G × E studies did not identify the specific environmental factor(s) responsible for the observed variations in starch properties among cultivars across locations and/or seasons. Air temperatures at certain stages of rice growth and development were specifically cited in some works ; this environmental factor will be discussed in the ensuing section.…”
Section: Genotype–environment Effects On Starch Structurementioning
confidence: 99%
“…The values of transition temperatures of MR lines were significantly differed from Koshihikari (65.9, 70.0, 77.1 °C), followed by IR36 (75.1, 79.1, 82.8 °C) ( P < 0.05). The higher GT and Δ H might be due to a higher degree of crystalline and molecular order in the endosperm . The variation in GT in starch from different cultivars may be due to differences in amounts of longer chains in amylopectin, since longer‐chain amylopectin requires a higher temperature to dissociate completely than that required for shorter‐chain amylopectin , .…”
Section: Resultsmentioning
confidence: 99%